The application of grain size trend analysis in the fine grained seabed sediment of Alexandroupolis Gulf. - Karditsa, A.; Poulos, S. E. (Bulletin of the Geological Society of Greece, 2013)
Grain size trend analysis is a method that determines sediment transport direction, based on the relationship of grain size parameters (mean size, sorting, skewness). The application of the method in the seabed sediments of Alexandroupolis Gulf showed that there are three different sub areas of distinctive sediment movement of bottom sediments (water depths <40 m):(i) the eastern part, which is mainly influenced by the Evros river water/sediment influxes; (ii) the central part that is primarily controlled by the wave activity; and, (iii) the western part that is mainly influenced by the wind driven and/or thermo-saline coastal circulation.